Politics of Strategic Decision Making in High-Velocity Environments: Toward a Midrange Theory - Eisenhardt, Kathleen M.; Bourgeois, L. J. (Academy of Management Journal, 1988)
How do politics affect the strategic decision processes of top executives in the ?high-velocity? microcomputer industry? We induced a midrange theory linking power, politics, and performance from a study of eight firms in the microcomputer industry. We found that politics?the observable, but often covert, actions by which executives enhance their power to influence decisions?arise from power centralization. Autocratic CEOs engage in politics and generate political behavior among subordinates. We also found that politics are not organized into shifting and temporary alliances based on issues. Rather, they are organized into stable coalitions based on demographic characteristics such as age and office location. Finally, politics within top management teams are associated with poor firm performance.